Paramedics' Perspectives on Factors Impacting On-Scene Times for Trauma Calls. Issue 3 (6th May 2018) - Levitan, Mark; Law, Madelyn P.; Ferron, Richard; Lutz-Graul, Karen
Abstract: Introduction: According to Ontario, Canada's Basic Life Support Patient Care Standards, Emergency Medical Services (EMS) on-scene time (OST) for trauma calls should not exceed 10 minutes, unless there are extenuating circumstances. The time to definitive care can have a significant impact on the morbidity and mortality of trauma patients. This is the first Canadian study to investigate why this is the case by giving a voice to those most involved in prehospital care: the paramedics themselves. It is also the first study to explore this issue from a complex, adaptive systems approach which recognizes that OSTs may be impacted by local, contextual features. Problem: Research addressed the following problem: what are the facilitators and barriers to achieving 10-minute OSTs? Methods: This project used a descriptive, qualitative design to examine facilitators and barriers to achieving 10-minute OSTs on trauma calls, from the perspective of paramedics. Paramedics from a regional Emergency Services organization were interviewed extensively over the course of one year, using qualitative interviewing techniques developed by experts in that field. All interviews were recorded, transcribed, and entered into NVivo for Mac (QSR International; Victoria, Australia) software that supports qualitative research, for ease of data analysis. Researcher triangulation was used to ensure credibility of the data. Results: Thirteen percent of the calls had OSTs that were less than 10 minutes. The following six categories were outlined by the paramedics as impacting the duration of OSTs: (1) scene characteristics; (2) the presence and effectiveness of allied services; (3) communication with dispatch; (4) the paramedics' ability to effectively manage the scene; (5) current policies; and (6) the quantity and design of equipment. Conclusion: These findings demonstrate the complexity of the prehospital environment and bring into question the feasibility of the 10-minute OST standard.M Levitan, MP Law, R Ferron, K Lutz-Graul .Paramedics' perspectives on factors impacting on-scene times for trauma calls .Prehosp Disaster Med .2018 ;33 (3 ):250 –255 .